2023
DOI: 10.3390/jcm12134233
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Headache: A Review of Prevalence, Clinical Features, Risk Factors, and Treatment Strategies

Abstract: Post-traumatic headache (PTH) is a common and debilitating consequence of mild traumatic brain injury (mTBI) that can occur over one year after the head impact event. Thus, better understanding of the underlying pathophysiology and risk factors could facilitate early identification and management of PTH. There are several factors that could influence the reporting of PTH prevalence, including the definition of concussion and PTH. The main risk factors for PTHs include a history of migraines or headaches, femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Worldwide, an estimated 69 million people suffer from TBI annually, of which around 80% are mTBI [27]. After mTBI, 37–69% of patients report PTH [5–7,8 ▪ ]. Migraine is one of the most common primary headaches with a prevalence of 14.0%, second only to TTH with a prevalence of 26.0% [7].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, an estimated 69 million people suffer from TBI annually, of which around 80% are mTBI [27]. After mTBI, 37–69% of patients report PTH [5–7,8 ▪ ]. Migraine is one of the most common primary headaches with a prevalence of 14.0%, second only to TTH with a prevalence of 26.0% [7].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…These relationships between PTH and migraine have led to questions about whether PTH attributed to mTBI is truly a distinct headache type, as opposed to a TBI worsening preexisting migraine or triggering migraine onset. The following sections provide an overview of the reasons for this debate and the evidence that PTH attributed to mTBI is a distinct headache type, adding several critical aspects to the excellent reviews of PTH in the last few years [8 ▪ ,9,10]…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological therapies are used for tension- and migraine-like headaches in PTH patients, including analgesics and non-steroidal anti-inflammatory agents ( Heyer and Idris, 2014 ; Mavroudis et al, 2023 ). Interestingly, although analgesics and non-steroidal anti-inflammatories can be prescribed for the acute phase of PTH, one study showed that acute administration of ibuprofen, acetaminophen, or both did not decrease the incidence of headaches seven days after injury in children and youth (aged 5–18 years) ( Ledoux et al, 2022 ).…”
Section: Pathophysiology Of Pth and Associated Mechanisms After Tbimentioning
confidence: 99%
“…At initial rehabilitation, the assessment included history, orthopedic tests, neurological testing, balance assessment, and grip strength, measured along with visual range of motion (ROM) for pain and full-spine upright radiography. The patient reported near-constant head pain measured on the HDI (98/100), indicating severe disability [ 10 ]. Constant NP-causing disability found using the NDI (64/100) indicated severe disability [ 11 ].…”
Section: Case Presentationmentioning
confidence: 99%